2015
DOI: 10.9734/ejnfs/2015/11557
|View full text |Cite
|
Sign up to set email alerts
|

Short Review of Sulphites as Food Additives

Abstract: Sulphites or sulphiting agents refer to sodium hydrogen sulphite, sodium metabisulphite, potassium metabisulphite, calcium sulphite, calcium hydrogen sulphite, and potassium hydrogen sulphite. As food additives, they are widely used by the food industry with a variety of commercial uses in food and beverages. Sulphites are effective bleaching agents, antimicrobials, oxygen scavengers, reducing agents, and enzyme inhibitors. Wine, beer, dehydrated fruits and vegetables, jam, juice, sugar, processed potatoes, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…For example, sulfites cause degradation of vitamin B1 (thiamine) in food, an essential nutrient [6].…”
mentioning
confidence: 99%
“…For example, sulfites cause degradation of vitamin B1 (thiamine) in food, an essential nutrient [6].…”
mentioning
confidence: 99%
“…For centuries, sulte has been extensively used as a preservative agent in the food industry, and beverages, in addition to some pharmaceutical products. 1,2 The role of sulte is to prevent oxidation, browning occurring via enzymatic and nonenzymatic reactions, and bacterial growth in such products. 3 Sulte has a negative effect on human health, especially for people suffering from sulte oxidase deciency disease.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some authors suggested that also glyosidic linkages of uridine and cytidine might be cleaved by sulfites (Figure 3‐7; Garcia Fuentes, Wirtz, Vos, & Verhagen, 2015). On the contrary, sulfites seem to not affect biogenic amines formation and accumulation.…”
Section: Chemical and Biochemical Propertiesmentioning
confidence: 99%